2002
DOI: 10.2134/jeq2002.8360
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Metrics and Estuarine Sediment Contamination in the Mid‐Atlantic and Southern New England Regions

Abstract: In a previously published study, quantitative relationships were developed between landscape metrics and sediment contamination for 25 small estuarine systems within Chesapeake Bay. These analyses have been extended to include 75 small estuarine systems across the mid-Atlantic and southern New England regions of the USA. Because of the different characteristics and dynamics of the estuaries across these regions, adjustment for differing hydrology, sediment characteristics, and sediment origins were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…Similar relationships have been found in other EMAP research (Weisberg et al 1992;Paul et al 1999;NCCR 2001;Paul et al 2002). With all regions pooled there was a consistent relationship between estuarine condition and urban development.…”
Section: Discussionsupporting
confidence: 87%
“…Similar relationships have been found in other EMAP research (Weisberg et al 1992;Paul et al 1999;NCCR 2001;Paul et al 2002). With all regions pooled there was a consistent relationship between estuarine condition and urban development.…”
Section: Discussionsupporting
confidence: 87%
“…The local watershed of a subestuary can be a source of stressors, such as suspended sediment, nutrients, and colored dissolved organic matter; many studies have demonstrated that watershed characteristics affect the condition of estuarine organisms and communities (Comeleo et al 1996;Paul et al 2002;DeLuca et al 2004;King et al 2005;Bilkovic et al 2006). Land cover characteristics of watersheds can be strong indicators of degraded benthic communities (Hale et al 2004).…”
Section: Influence Of Landscape Factors On Sav Abundance Among Subestmentioning
confidence: 99%
“…Watershed land cover can affect SAV by elevating nutrient and sediment loading to estuaries (Staver et al 1996), and SAV responses to watershed inputs have been considered in modeling estuarine water quality (Cerco and Cole 1993;Cerco 1995;Cerco and Moore 2001). Nonpoint source discharges of sediment and nutrients from watersheds go up with increasing proportions of either agricultural or developed lands (Frink 1991;Comeleo et al 1996;Jordan et al 1997aJordan et al ,b, 2000Jordan et al , 2003Paul et al 2002;Weller et al 2003) and croplands discharge far more nitrogen than other rural land covers (Beaulac and Reckhow 1982;Jordan et al 1997a,b). There are several possible sources of nutrients in developed land, including septic systems (Weiskel and Howes 1992;Nizeyimana et al 1996;Short and Burdick 1996), sewage system leaks, lawn fertilizers, and industrial activity (Cerco et al 2002).…”
Section: Influence Of Landscape Factors On Sav Abundance Among Subestmentioning
confidence: 99%
See 2 more Smart Citations